Olfaction and neurocognition after COVID-19: a scoping review - Vilarello, Brandon J.; Jacobson, Patricia T.; Tervo, Jeremy P.; Waring, Nicholas A.; Gudis, David A.; Goldberg, Terry E.; Devanand, D. P.; Overdevest, Jonathan B. (Frontiers in Neuroscience, 2023)
Introduction: COVID-19 induces both acute and chronic neurological changes. Existing evidence suggests that chemosensory changes, particularly olfactory loss, may reflect central neurological dysfunction in neurodegenerative diseases and mark progression from mild cognitive impairment to Alzheimer’s. This scoping review summarizes the available literature to evaluate the relationship between neurocognition and olfaction in young to middle-aged adults with minimal comorbidities following COVID-19 infection. Methods: A literature search of PubMed, Ovid Embase, Web of Science, and Cochrane Library was conducted. Studies underwent title/abstract and full-text screening by 2 reviewers, with a third reviewer resolving any conflicts. Remaining studies underwent data extraction. Results: Seventeen studies were eligible for data extraction after the review process, where twelve studies found significantly poorer cognition in those suffering from olfactory dysfunction, four studies showed no association between cognition and olfaction, and one study reported lower anosmia prevalence among patients with cognitive impairment. Conclusion: The majority of studies in this review find that olfactory dysfunction is associated with poorer cognition. More rigorous studies are needed to further elucidate the relationship between olfaction and cognition after COVID-19.